2021
DOI: 10.3389/fpls.2021.663943
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Postharvest Tomato Fruit Ripening by Endogenous Salicylic Acid

Abstract: Exogenous application of salicylic acid (SA) has been known for delaying ripening in many fruit and vegetables. But the function of endogenous SA in relation to postharvest fruit performance is still unexplored. To understand the role of endogenous SA in postharvest fruit ripening of tomato, 33 tomato lines were examined for their endogenous SA content, membrane stability index (MSI), and shelf life (SL) at turning and red stages of tomato fruit ripening. Six tomato lines having contrasting shelf lives from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 116 publications
0
15
0
Order By: Relevance
“…Based on this, approaches have been developed to delay the process of fruit ripening and lessen the nutrition loss, including refrigeration control, atmosphere modification (fumigation with exogenous NO, H 2 S, H 2 O 2 , etc.) and chemical substance treatment such as ethylene inhibitor, methyl jasmonate and salicylic acid [ 45 , 46 , 47 , 48 , 49 ]. In the present study, we applied H 2 S produced by NaHS to explore its function in tomato flavor and nutrient regulation after harvest.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this, approaches have been developed to delay the process of fruit ripening and lessen the nutrition loss, including refrigeration control, atmosphere modification (fumigation with exogenous NO, H 2 S, H 2 O 2 , etc.) and chemical substance treatment such as ethylene inhibitor, methyl jasmonate and salicylic acid [ 45 , 46 , 47 , 48 , 49 ]. In the present study, we applied H 2 S produced by NaHS to explore its function in tomato flavor and nutrient regulation after harvest.…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous applications of melatonin, sucrose and several plant hormone molecules such as ethylene, abscisic acid, brassinolide, and methyl jasmonate accelerate postharvest tomato fruit ripening [ 9 , 25 , 26 , 27 , 28 , 29 ]. In contrast, nitric oxide, ethanol and other plant hormones like gibberellic acid (GA 3 ) and salicylic acid have been demonstrated to delay tomato fruit ripening [ 2 , 30 , 31 , 32 ]. In this study, we found that RA, a natural polyphenol derived from the Rosmarinus plants, delayed fruit ripening and extended tomato fruit shelf life with less detrimental impacts on fruit quality.…”
Section: Discussionmentioning
confidence: 99%
“…0.25 mM MeJA and 4 mM SA significantly preserved firmness of strawberry (66). Salicylic acid treatment decreased pectin methyl esterase resulting in texture firmness retention (67).…”
Section: Firmness Of Cantaloupe Affected By Pre-harvest and Postharvest Treatment With Methyl Jasmonate And Salicylic Acidmentioning
confidence: 91%
“…MeJA treatment improved the lycopene accumulation via accelerating carotenoid biosynthetic route gene exhibition (88). SA treatment was beneficial to improve the carotenoid content in mandarin fruit lycopene accumulation was strictly correlated with high salicylic acid concentration (67).…”
Section: Carotenoid Of Cantaloupe Affected By Pre-harvest and Post-harvest Treatment With Methyl Jasmonate And Salicylic Acidmentioning
confidence: 93%